TOURISM AS REFLECTED IN TRAVELLING WOMEN: A COMPARATIVE CULTURAL STUDY ON THE NOVELS OF DAISY MILLER, A PASSAGE TO INDIA, AND PADA SEBUAH KAPAL - Hartiningsih, Sri; Ardika, I Wayan; Kutha Ratna, I Nyoman; Paramartha, I Gde (E-Journal of Cultural Studies; Vol. 3, No. 2 Juli 2009, 2012)
Travelling has occurred since a long time ago. Travelling is not only done by men butalso by women. In relation to travelling, travelling done by women is examined, especially thelandlady’s environment, as there is a relationship between the host and the guest. The researchproblems are (1) how is reflection of tourism in the travelling women portrayed on the novels ofDaisy Miller, A Passage to India, and Pada Sebuah Kapal?. (2) How are motivating andattracting factors related to tourism as reflected in the travelling women articulated on the novelsof Daisy Miller, A Passage to India, and Pada Sebuah Kapal?. (3) How do cultural barriersoccur in tourism as reflected in the travelling women on Daisy Miller, a Passage to India, andPada Sebuah Kapal novel? In general, this research is to find out the comparison of travellingdone by women. Specifically, it is to discover the reflection of tourism, how the motivating andattracting factors and cultural barriers occur in tourism as reflected in the travelling done bywomen.This research is conducted on three novels, Daisy Miller written by Henry James, APassage To India by E.M. Forster, and Pada Sebuah Kapal by NH. Dini called comparativeliterature showing the continents of America, Europe and Asia. Discussing the three continents,this research is called global literature. Hermeneutic method was used to interpret the content ofthose three novels by employing deconstruction, postcolonial and feminism theories. The maindata were taken from those novels and the location of the research was both at private librariesand state libraries or institutions and websites. To support the main data, secondary data werealso needed, which in this case, were obtained by interviewing the women who have travelledabroad. Then the results were formally and informally presented.The findings show that the reflection of tourism in travelling done by women is representedby family companion, and that the means of transportation to their destinations are indigenousmeans of transportation and that the tourist objects visited are art metamorphosis, travel hyperreality,sacred places and natural and human recreational places. The factors motive ting thewomen to travel are inter personal, cultural, status and prestige. The things making theminterested in travelling are: the Castle of Chillon in Switzerland and the regions’s history, theevening party in Italy as a tradition to welcome new people, the architectures of Caesars’Palaces, the Coliseum and Chandrapore club as a tradition to welcome new people, the bridge party to know the language spoken and dress worn – traditional costumes of India, Koyasan asBuddhist religion and Paris as the centre of dress model. Cultural barriers refer to differentetiquettes, ideologies and moral values resulting in different ways of travelling and theirsolutions.Knowing the culture of the destination that is going to be visited is really needed, at least inorder not to know nothing at all about such a destination; furthermore, it reduces culturalbarriers. That is why cross cultural understanding is really necessarily given not only to thedoers of tourism but also to all institutions in order to reduce misunderstanding and increaseappreciation towards each other.
Keywords: reflection, travelling women, motivating and attracting factors, cultural barriers